Cumulative live birth rates and perinatal outcomes with the use of time‐lapse imaging incubators for embryo culture: a retrospective cohort study of 1882 ART cycles. (12th March 2018) - Mascarenhas, M; Fox, SJ; Thompson, K; Balen, AH
Abstract : Objective: Comparison of live birth rates and the perinatal outcomes after fresh and frozen embryo transfer between time‐lapse imaging (TLI) and standard culture (SC) incubators. Design: Retrospective cohort study. Setting: A single tertiary level IVF unit. Population: Women undergoing IVF between January 2014 and October 2015. Methods: Comparison was done between 1064 IVF cycles using TLI (TLI cycles) and 818 IVF cycles using SC (SC cycles). Main outcome measures: Cumulative live birth rate per oocyte retrieval and perinatal outcomes including birthweight, gestational age, preterm birth (PTB) (<37 weeks), early preterm birth (PTB; <32 weeks), low birthweight (LBW; <2500 g), very LBW (<1500 g) and macrosomia (>4500 g). Results: The fresh embryo transfer live birth rate was noted to be higher for TLI cycles [TLI 36.8 versus SC 33.9%, adjusted odds ratio (aOR) 1.28, 95% CI 1.05–1.57], but the frozen embryo transfer live birth rates were not significantly different. The mean birthweight was higher in the TLI group after both fresh [adjusted mean difference (aMD) 174.78 g, 95% CI 64.80–284.77] and frozen embryo transfers (aMD 175.91 g, 95% CI 16.98–334.84). After a fresh embryo transfer, there was a lower risk of early PTB and very LBW in the TLI group. Among frozen embryo transfers, there was a lower risk of early PTB and LBW in the TLI group. Conclusions: TLI incubators are associated with improved perinatal outcomes and higher mean birthweight after fresh and frozen embryo transfer. Tweetable abstract: Time‐lapse imaging incubators in IVF improve perinatal outcomes after both fresh and frozen embryo transfers. Tweetable abstract: Time‐lapse imaging incubators in IVF improve perinatal outcomes after both fresh and frozen embryo transfers.